Global value chains in agriculture and food (OECD Publishing, 2020)
This report synthesises the key findings and policy messages from recent OECD work on global value chains (GVCs) in agriculture and food. The food and agriculture sector is increasingly organised within GVC around a number of global hubs. Agro-food GVCs have broadened the gains from specialisation and trade through stronger sector and employment growth. Openness to trade, especially services trade, can positively influence domestic value added creation in agro-food GVCs. However, trade protection and distorting agricultural support policies can reduce the gains from GVC participation and impose costs along the value chain. Government policies need to focus on facilitating participation in GVCs and helping to manage any adjustments across the food and agriculture sectorKeywords: Agro-food, value added, employment, policy reform, trade.
10.1787/6e3993fa-en
Keywords: Amtsdruckschrift; Graue Literatur; Agriculture and Food; Global value chains; agricultural trade; trade in value added; services; employment; policy reform